Association between triglyceride glucose index and endometriosis in adults in the United States: A comprehensive study from the National Health and Nutrition Examination Survey (NHANES). - Sasa Gao; Xiaoping Cui (PLoS ONE)
Background The triglyceride glucose (TyG) index has been well recognized as a reliable marker of insulin resistance and substantially correlated with the pathogenesis and progression of hypertension and cardiovascular diseases. However, no study has investigated the association between the TyG index and endometriosis. Therefore, this study aimed to uncover an association between the TyG index and endometriosis. Methods This cross-sectional investigation employed the extensive dataset derived from the National Health and Nutrition Examination Survey (NHANES) (1999-2006). To explore the potential connection between the TyG and endometriosis, a multivariate weighted logistic regression model was established. The nonlinear relationship between the TyG index and the risk of endometriosis was explored using restricted cubic spline models (RCS). Furthermore, subgroup analyses were conducted. Results Ultimately, 2,508 individuals were included in this investigation. The findings unveiled a robust positive correlation between the TyG index and the susceptibility to endometriosis (OR [95% CI]: 1.52 [1.024,2.258]; P < 0.05). This positive association remained consistent across diverse subgroups. Age, birthplace, and whether one ovary was removed were identified as significant risk factors. In RCS analysis, the TyG index showed a nearly linear relationship with the risk of endometriosis (P-nonlinear > 0.05). Conclusions The findings indicate a positive association between the TyG index and the risk of endometriosis, exhibiting an approximate non-linear relationship.